Bakuman Sebagai Simulakra Industri Komik Bagi Komikus di Indonesia - Johanes Park (ULTIMART Jurnal Komunikasi Visual, 2022)
Bakuman is a manga about 2 main characters named Moritaka Mashiro and Akito Takagi who have dreamed to become a popular manga artist and story writer. Bakuman manga, tells the stories about the main characters’ career path from amateur to professional which engage the readers to become a mangaka (comic artist). The purpose of this research was to find out the impact of Bakuman manga as simulacra of the comic industry in Indonesia. The population consisted in this research was 100 digital comic artists in Indonesia (66 male, 34 female) with a range of 19 to 39 years old audiences. The comic artist filled out a questionnaire that spread on social media. The comic artist who participated in this research was obtained by searching Indonesian comic artist communities and a list of the official comic authors in Line Webtoon and Ciayo Comics. The questions in the research were based on text analysis with AIDA theory as measurement. Text analysis based on the main character traits, comic artworks quality standards, achievements of the main character, comic artist work patterns, and the state of the comic industry in Bakuman manga. From this research, it can be proven that after reading Bakuman manga, the readers are inspired to become comic artist by creating and publishing comics in Indonesia. Because digital comic artists in Indonesia are inspired by Bakuman manga, the ideal state of comic culture and industry refers to the situation in Bakuman manga. Keywords: manga; bakuman; Indonesia; comic; artists; simulacra; media